Australian general practitioners' views regarding providing nutrition care: results of a national survey. (November 2016) - Crowley, J.; O'Connell, S.; Kavka, A.; Ball, L.; Nowson, C.A.
Abstract: Background: The prevalence of chronic disease is considerable, and dietary behaviours influence the progression of many chronic diseases. Practice guidelines recommend that general practitioners (GPs) promote healthy dietary behaviours in relevant consultations with patients in order to improve health outcomes at a population level. Objective: To describe GPs' perceived interest, confidence and barriers to support patients to have a healthy diet. Method: A 24-item online and written survey was distributed in a national weekly newsletter to GPs in Australia. Results were descriptively analysed and investigated for associations with GPs' demographic characteristics. Results: A total of 322 GPs responded to the survey. Nearly all ( n = 295, 91.6%) were interested in supporting patients to eat well, and most ( n = 231, 71.7%) reported moderately high confidence for providing nutrition care with clear public health messages for conditions, such as cardiovascular disease. Many GPs ( n = 170, 52.8%) cited lack of time as the biggest barrier to providing nutrition care, and the overwhelming majority ( n = 289, 89.8%) were interested in receiving additional education and training to enhance their nutrition knowledge and skills. Discussion: Many GPs are interested in nutrition and would benefit from educational programmes that improve their competence to provide nutrition care. Professional development opportunities should focus on the identification of nutritional risk and the promotion of healthy dietary behaviours within the time constraints of a standard consultation. Highlights: General practitioners require sufficient knowledge, positive attitudes and effective approaches to provide nutrition care. Action is required to address this issue in medical training and general practitioners' (GP) training to include nutrition care in practice. GPs could be effective in supporting patients' nutrition behaviours and reducing the burden of disease in Australia.